Pengaruh Media Alphabet Card terhadap Minat Baca Siswa Kelas II SDN 06 Perawang Barat - Elsa Okta Revani; Dea Mustika (Journal on Education, 2024)
This study aims to determine the effect of picture card media on students' reading interest. The form of research used is quantitative research. The sample taken was 54 consisting of experimental class and control class. The instruments used were questionnaires and observations. Validity test and reliability test were used in testing the instrument. The significance test was carried out in 2 stages, namely homogeneity test and homogeneity test. Hypothesis test consisting of t-test and descriptive reliability test. The results of this study are (1) there is an effect of picture card media on students' reading interest, with a significance result of 0.000 <0.05 from the hypothesis test by conducting a descriptive reliability test, (2) by conducting a t-test obtained a significance value of 0.000 <0.05 which means that the independent variable and dependent variable have an influence. This shows that picture card media (X) on reading interest (Y) has a significant effect. So it is very possible to conclude that there is an influence between Alphabet Card Media and Reading Interest.